Advantages, Challenges and Prospects of ChatGPT in Oral English Teaching - Shi, Xiaoqin (Transactions on Social Science, Education and Humanities Research, 2024)
With the development of artificial intelligence, ChatGPT has set off a hot wave in various fields, and brings opportunities and challenges to education. The positive and negative effects of ChatGPT on education have aroused heated discussion in academic circles. Based on its principle and development process, and the continuous optimization of language model, ChatGPT can play a unique advantage in oral English teaching, such as: providing personalized oral practice, real-time error correction and feedback, real dialogue simulation, safe and comfortable dialogue environment. At the same time, the challenge of ChatGPT in oral teaching is also the direction of its future technological improvement, such as: real-time communication of spoken language, recognition of voice tone and intonation, integration with VR technology, autonomous assessment of spoken language level, etc., Those can become the application prospects of ChatGPT in oral teaching. Artificial intelligence assisted oral teaching is a new mode of oral teaching.